Costas Loops Theory, Design, and Simulation - Best, Roland (Springer International Publishing : Imprint: Springer, 2018)
This book guides engineers through the use of the Costas loop, which can be considered an extension of the better known Phase-locked loop. The author discusses all three variants of the Costas loop and describes their dynamic behavior, using newly developed mathematical models. Step-by-step design procedures and Simulink models are included for every type of Costas loop. These models enable designers to test circuits prior to building breadboards or prototypes, accelerating the design process considerably. Discusses in detail all existing variants of Costas loops, including their dynamic behavior; Links theory and practice by including design procedures and Simulink models for every type of Costas loop; Describes all relevant modulation schemes used in Costas loops, such as BPSK (binary phase shift keying), QPSK (quadrature phase shift keying), mPSK (m-ary phase shift keying), and QAM (quadrature amplitude modulation).